CRITIQUE OF MILITARY REASON. LEOPOLD BUCZKOWSKI AS AN ILLUSTRATOR - Polit, Paweł (Prace Polonistyczne, 2024)
The article explores the thematic and technical diversity of images created by Leopold Buczkowski and used by him as illustrations of his own and other authors’ literary works. This diversity results from a general idea that informs his works and challenges the rigid distinction between the image and the word. In Buczkowski’s oeuvre, the proliferation of images corresponds to the proliferation of statements made by the characters of his literary works, and formulated using various conventions. In his artistic practice, he sometimes combined prose and visual expression, revealing the nature of the relationship between them. The article examines this connection – it comments on the “second-hand” nature of illustrations made by Buczkowski for his own texts and compares them with his illustrations made for texts of other authors and with his other visual works that are not related to any specific texts. It argues that Buczkowski’s images look as if they were borrowed from an image repository, thus resembling quotations.